THE IMPACT OF MILITARY AND ECONOMIC SHOCKS ON HUMAN RESOURCES IN THE MANAGEMENT SYSTEM OF INDUSTRIAL ENTERPRISES (INNOVATIVE ECONOMY, 2025)
Huk V.V.  THE IMPACT OF MILITARY AND ECONOMIC SHOCKS ON HUMAN RESOURCES IN THE MANAGEMENT SYSTEM OF INDUSTRIAL ENTERPRISESPurpose. The aim of the article is to diagnose the impact of military and economic shocks on the human resources of industrial enterprises in Ukraine and to develop management recommendations to increase their resilience.Methodology of research. The methodological basis is a systematic and comparative approach to the analysis of the labour market and HR practices in industry. The analysis of statistical data from international organizations and national institutions (OECD, KSE, Bank of Israel, DTDA, US–Ukraine Business Council, Frontliner) was used, the results of modern scientific works on personnel management in crisis and war conditions were summarized, and the Ukrainian experience was compared with the practices of other countries experiencing armed conflicts or deep economic shocks.Findings. It is shown that the combination of military and economic shocks creates double pressure on labour supply and demand: mass mobilization, external and internal migration, and the destruction of the industrial base lead to an acute shortage of personnel, a change in the gender and professional structure of employment, and an increase in labour costs, while a decline in demand, financial difficulties, and the destruction of logistics limit the possibilities for job creation. Based on Ukrainian data, the scale of personal losses and structural shifts in the labour market are characterized, in particular, the redistribution of vacancies between sectors and the increase in demand for blue-collar professions, defence specialists, and mental health specialists. A comparison with the experience of Israel and the lessons of the COVID-19 pandemic allowed us to show common features (labour shortage, reassessment of the importance of flexible forms of employment, digitalization of HR processes) and differences in the dynamics of unemployment and wages. The tools for adapting industrial enterprises to personnel shortages and uncertainty (internal mobility and retraining, digitalization of personnel management, mental health support, work with vulnerable groups) have been systematized and eight key areas for improving HR management in conditions of prolonged shocks have been formed.Originality. The content of the category “military-economic shocks” in relation to the management of human resources of industrial enterprises has been clarified, a conceptual framework for analysing HR systems through the prism of supply shocks (mobilization, migration, destruction of infrastructure) and demand shocks (decline in production, quarantine restrictions, decline in investments) has been proposed. For the first time, based on the integration of macroeconomic indicators, labour market data and practices of individual countries, the complex impact of military and economic shocks on the human resources of industrial enterprises of Ukraine has been systematically described.Practical value. The proposed approaches and recommendations can be used by heads of industrial enterprises, HR directors, personnel services specialists and state authorities when developing recovery and development strategies in the war and post-war periods. The formulated directions of action create a practical basis for strengthening the resilience of HR systems of industrial enterprises and reducing long-term losses of human capital.Key words: labour market, personnel shortage, digitalization of personnel management, mobilization, external and internal migration, structural shifts in the labour market, redistribution of vacancies.
Keywords: labour market; personnel shortage; digitalization of personnel management; mobilization; external and internal migration; structural shifts in the labour market; redistribution of vacancies